Rhetoric and realities in Australian universities of student engagement in online learning: Implications for a post-pandemic era - Parida, Subhadarsini; Dhakal, Subas; Dayaram, Kantha; Mohammadi, Hossein; Ayentimi, Desmond; Amankwaa, Albert; D'Cruz, Denise (Elsevier, 2023)
The issue of student engagement in online learning (SEOL) environments which gained attention during the COVID-19 pandemic, continues to be a significant topic of interest in the innovative scholarship of teaching and learning space within business schools. This paper explores academic perspectives on the rhetoric and realities of SEOL in Australian universities. The study employs an exploratory qualitative research approach utilising interview (n = 33) data and content analysis of university policies and documents. The findings highlight technological hurdles, administrative negligence, piecemeal professional development initiatives, and policy ambiguities impeding SEOL. The paper discusses the implications of these findings in the context of the professional development of academics in a post-pandemic era. The paper makes broader analytical contributions toward evaluating the implementation of SEOL-related policies in Australian universities and beyond.